Fractured tales : invisibles in Indian democracy - Badri Narayan (Oxford University Press, 2016)
"Fracture Tales documents narratives of the voiceless and invisible dalit castes that have been left out in the 60 years of state-led Indian democracy. Exploring the deepening of democracy among the dalits of Uttar Pradesh, it argues that the process of democratization of these communities over-represents some groups such as the Chamars and Pasis while neglecting others like the Musahar, Bansphor, and Sapera communities"--Page [4] of cover.